Strong primary care and patients’ survival - Wensing, Michel; Szecsenyi, Joachim; Kaufmann-Kolle, Petra; Laux, Gunter (Scientific reports, 2019)
Primary healthcare is the cornerstone of any healthcare system. A major health system reform to strengthen primary care has been implemented in Germany since 2008. Key components include: voluntary participation, intensive management of patients with chronic diseases, coordination of access to medical specialists, continuous quality improvement, and capitation-based reimbursement. The objective of this study was to assess the effect of this reform on survival of enrolled patients. We conducted a comparative cohorts study with 5-year follow-up, starting in the year 2012 in Baden-Wuerttemberg, Germany. Participants were 1,003,336 enrolled patients and 725,310 control patients. A Cox proportional hazards regression model was applied to compare survival of enrolled patients with a composed control cohort of non-enrolled patients, adjusted for a range of patient and physician characteristics. Average age of enrolled patients was 57.3 years and 56.1% were women. Compared to control patients, they had lower mortality (Hazard Ratio: 0.978; 95% CI: 0.968; 0.989). Participation in chronic disease management programs had independent impact on survival rate (Hazard Ratio 0.744, 95% CI: 0.734; 0.753). We concluded that strong primary care is safe and potentially beneficial in terms of patients’ survival.
Gesehen am 30.10.2019